E-Commerce and M-Commerce Boom: The Urgent Need for Patent Law Reform in Indonesia - Abdul Atsar; Nakzim Khalid Siddiq; Lalu Achmad Fathoni; Rina Apriani; Erika Putri Ramadhani (Universitas Negeri Semarang, 2025)
The rapid expansion of e-commerce and mobile commerce (m-commerce) in Indonesia has transformed the business landscape, offering new opportunities but also presenting significant legal challenges. With the rise of digital platforms and mobile applications, intellectual property issues, particularly those related to patents, have become increasingly complex. Indonesia's current patent law, rooted in the Patent Law No. 13 of 2016, is struggling to keep pace with the fast-evolving nature of these industries. This study examines the urgent need for patent law reform in Indonesia to address the unique challenges posed by e-commerce and m-commerce innovations, including digital platforms, mobile applications, and software-based inventions. The article argues that the existing legal framework fails to adequately protect new technological advancements, leaving gaps that allow for patent disputes, weak enforcement, and a lack of clarity regarding patent eligibility in the digital economy. By analyzing key issues such as patentability criteria, infringement protection, and cross-jurisdictional patent enforcement, this study proposes targeted reforms to align Indonesia's patent law with international standards, particularly in jurisdictions with robust digital patent protection frameworks, such as the European Union and the United States. The contribution of this study lies in offering a comprehensive analysis of Indonesia's patent law in the context of e-commerce and m-commerce growth, advocating for a legal overhaul that fosters innovation, encourages investment, and ensures stronger protection for digital inventions. These reforms are essential for Indonesia to maintain its competitive edge in the global digital economy.